The Incidence of Anastomotic Leaks in a South African Healthcare Setting - Karimbocus, Mohammad (Division of General Surgery, 2023)
Introduction AL is known to be associated with increased morbidity and mortality. There are no studies reporting AL rate in sub-Saharan Africa. Methods A prospective multicentre snapshot study of 145 patients across the Cape Metro West healthcare platform was performed from 01/09/2020 to 31/12/2020. The study included all patients who had one or more intestinal anastomoses beyond the ligament of Treitz and excluded patients under 18 and patients undergoing simple appendectomies. Leaks were diagnosed clinically, radiologically or at relook laparotomy, outcomes and 30-day mortality were recorded. Results 102 males and 43 females were recruited, with a mean age of 41.9 years. 35 elective and 110 emergency procedures were performed. 120 patients had an uneventful postoperative course. 25 patients were investigated for AL and 15 leaks were confirmed. The overall leak rate was 10.3%, the leak rate for elective procedures was 8.6% and 10.9% for emergency procedures. 4 patients were diagnosed clinically, 4 were diagnosed at relaparotomy while 7 were found to have leaks on CT scans. 7 patients with AL needed a stoma, 1 needed a percutaneous drain, and 6 were treated conservatively. There were 3 deaths (overall mortality rate 2.07%), 1 in the AL group (mortality rate 6.67%), and 2 in the patients with no AL (1.54%). Conclusion This is the first study to look at AL in South Africa and it illustrates surgical practice across the entire healthcare platform. Anastomoses were performed safely in our healthcare service with a leak rate comparable to previous international studies.